Економічне підґрунтя деолігархізації в Україні - Kolosov, Andriy (Contemporary trends in business security: Problems and challenges of eastern economies, 2022)
In Ukraine, which remains in last place in Europe in terms of gross domestic product (GDP), controversy unfolded on overcoming the oligarchy as the most important systemic problem of economic relations in the country. It is because of the monopoly of oligarchic structures in the energy sector in Ukraine that it is not possible to complete the reform of the energy market, when the interests of monopoly companies are dominated by public interests, destroying the established foundations for the introduction of market relations. Unlike the oligarchy in Poland, in which rich Poles either made their own fortune or got a family business, Ukrainian oligarchs were formed as a result of the inept privatization of property of state-owned enterprises in the most important sectors of the economy, in particular in the energy sector. The most threatening is the huge influence of the oligarchic companies in Ukraine on the adoption of state decisions, as well as the constant desire to use the possibilities of the state budget of the country in their favor.The oligarchic structure of the Ukrainian economy arose as a result of the shortcomings of the privatization being carried out in the country, the actual result of which was the deprivation of state ownership of the property of enterprises in favor of non-state capital. The government left without control the further purchase of privatized enterprises and their shares, creating the basis for the formation of an oligarchic economy, which was facilitated by a fairly high monopolization of the main sectors of the Ukrainian economy during his stay in the Soviet Union. Such initial conditions simplified the creation of oligarchic corporations as monopolists in certain sectors of the economy, and the assistance of state bodies in this process paved the way for the easy formation of vertical industrial complexes owned by oligarchs. In the ongoing controversy regarding the formulation of legislation on deoligarchization of the country, it should be taken into account that, in addition to overcoming the influence of the oligarchy on media and politics, it is necessary to seriously reform the ownership structure in the most important sectors of the economy in order to overcome monopoly in them and create equal conditions for competition between economic entities of various forms of ownership